Studi pembuatan kerupuk ikan oci (Rastrelliger sp) - Darman Kadir; Muh. Sudirman Akilie; Anto Anto (Jurnal Agercolere, 2021)
This study aims to determine the effect of using tapioca flour in the manufacture of fish crackers and determine the moisture content, ash content, texture of the analyzer, protein content and organoleptic test of oci fish crackers. The method used in this study was a simple completely randomized design (CRD) method with three replications with fish formulation of 175 g oci + 75 g tapioca flour, 125 g of oci fish + 125 g of tapioca flour with 125 g of oci fish + 125 g of tapioca flour and fish oci. 75 g + 175 g of tapioca flour, namely with 75 g oci fish formulation + 175 g tapioca flour. The results of the analysis of variance showed that the addition of tapioca flour had a significant effect on water, ash, protein, and garnish content. The organoleptic test results showed that the three treatments for aroma parameters were very favorable, grayish white color, slightly crunchy texture, and slightly preferred taste.